Tuning into Kids Training to Improve Emotion Coaching’s Skill of Mother With Early Childhood Children - Husna, Mai Tiza; Ambarini, Tri Kurniati (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Abstract: The aim of this study is to determine the effectiveness of Tuning in to kids training in improving the emotion coaching of mothers who have early childhood children. This research is a quasi experimental research with non randomized pretest - posttest control group design. The subjects of this study consisted of 20 people divided into two groups. Data collection was performed using Maternal Emotional Style Quastionnare scale (7 items) developed by Lagace-Seguin and Coplan (2005). Data were analyzed using Independent sample t-test. The result show that there are a significance difference emotion coaching’s score between experiment and control group. The training has a great effect in improving the emotion coaching of the mother.The final result of this study is Tuning in to kids training effectively improve emotion coaching of the mother with early childhood.